Genetics of panicle-related traits of agronomic importance in rice through triple test croá analysis - Saleem, M.Y.=700 1 Atta, B.M.; Cheema, A.A.; Haq, M.A.
(Es, En)
ilus., 25 ref.
Keywords: GENETICA; HIBRIDACION; ARROZ; GENES DOMINANTES; INTERACCION DE GENES; ESPAÑA; EFECTOS ADITIVOS